Nanotherapeutics for Treatment of Pulmonary Arterial Hypertension - Segura-Ibarra, Victor; Wu, Suhong; Hassan, Nida; Moran-Guerrero, Jose A.; Ferrari, Mauro; Guha, Ashrith; Karmouty-Quintana, Harry; Blanco, Elvin (Frontiers in Physiology, 2018)
Pulmonary arterial hypertension (PAH) is a devastating and fatal chronic lung disease. While current pharmacotherapies have improved patient quality of life, PAH drugs suffer from limitations in the form of short-term pharmacokinetics, instability, and poor organ specificity. Traditionally, nanotechnology-based delivery strategies have proven advantageous at increasing both circulation lifetimes of chemotherapeutics and accumulation in tumors due to enhanced permeability through fenestrated vasculature. Importantly, increased nanoparticle accumulation in diseased tissues has been observed pre-clinically in pathologies characterized by endothelial dysfunction and remodeled vasculature, including myocardial infarction and heart failure. Recently, this phenomenon has also been observed in preclinical models of PAH, leading to the exploration of nanoparticle-based drug delivery as a therapeutic modality in PAH. Herein, we discuss advantages of nanoparticles for efficacious treatment of PAH, including heightened therapeutic delivery to diseased lungs for increased drug bioavailability, as well as highlight innovative nanotherapeutic approaches for PAH.